Conversations with(in) the collective unconscious by consumers, brands, and relevant others - Woodside, Arch; Megehee, C.; Sood, S. (Elsevier, 2012)
Jung's (2009) paintings of his dreams to enable conscious interpretation of his conversations within the collective unconscious informs a call for creating visual narrative art to inform meanings of personal and collective unconscious relating to stories consumers tell about buying and using brands. This study describes13 conversations relevant to the study of conscious and the collective unconscious for consumer–brand relationships/communications. The 13 conversations' paradigm is useful for complementing the dominant logic by scholars of asking questions and relying on consumer conscious interpretations in their responses. The article advocates the use of multiple methods for both collecting and interpreting consumer–brand relationships, and illustrates the usage of storyboard-art of consumer–brand relationships in natural contexts. Brand strategy implications focus on the value of identifying how brands enable consumers to enact primal forces (archetypes).